(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Holy See and artificial intelligence: from the Rome Call for AI Ethics to the Vatican Guidelines The article analyses the Catholic Church’s positive action to promote a development of artificial intelligence that is compatible with the common good. In addition to the many interventions by Pope Francis, the Holy See in the Rome Call for AI Ethics identified a series of fundamental ethical principles for the construction of an artificial intelligence that respects human dignity. Representatives of other religious denominations have also adhered to this important document, placing the foundations of an algoretic elaborated through new practices of interreligious dialogue projected to promote the good of man beyond the frontiers of the digital world. The final section analyzes the Guidelines on artificial intelligence published by the Pontifical Commission for Vatican City State. SOMMARIO: 1. Chiesa cattolica, tecnologie digitali e sviluppo umano integrale - 2. Santa Sede, Rome Call for AI Ethics e bene comune interculturale - 3. Intelligenza artificiale, algoretica e nuove rotte del dialogo interreligioso nel continente digitale - 4. Le Linee guida in materia di intelligenza artificial introdotte dalla Pontificia Commissione per lo Stato della Città del Vaticano.